RHOB LINKS PDGF SIGNALING TO CELL MIGRATION BY COORDINATING ACTIVATION AND LOCALIZATION OF CDC42 AND RAC - Huang, Minzhou (2011)
The small GTPase RhoB regulates endocytic trafficking of receptor tyrosine kinases (RTKs) and the non-receptor kinases Src and Akt. While receptor–mediated endocytosis is critical for signaling processes driving cell migration, mechanisms that coordinate endocytosis with the propagation of migratory signals remain relatively poorly understood. In this study, we show that RhoB is essential for activation and trafficking of the key migratory effectors Cdc42 and Rac in mediating the ability of platelet-derived growth factor (PDGF) to stimulate cell movement. Stimulation of the PDGF receptor-β on primary vascular smooth muscle cells (VSMCs) results in RhoB-dependent trafficking of endosome-bound Cdc42 from the perinuclear region to the cell periphery, where the RhoGEF Vav2 and Rac are also recruited to drive formation of circular dorsal and peripheral ruffles necessary for cell migration. Our findings identify a novel RhoB dependent endosomal trafficking pathway that integrates RTK endocytosis with Cdc42/Rac localization and cell movement.